2018
DOI: 10.4254/wjh.v10.i6.425
|View full text |Cite
|
Sign up to set email alerts
|

Paracentesis in cirrhotics is associated with increased risk of 30-day readmission

Abstract: AIMTo determine the readmission rate, its reasons, predictors, and cost of 30-d readmission in patients with cirrhosis and ascites.METHODSA retrospective analysis of the nationwide readmission database (NRD) was performed during the calendar year 2013. All adults cirrhotics with a diagnosis of ascites, spontaneous bacterial peritonitis, or hepatic encephalopathy were identified by ICD-9 codes. Multivariate analysis was performed to assess predictors of 30-d readmission and cost of readmission.RESULTSOf the 595… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…It is then followed by the administration of diuretic agents and a low sodium diet[54]. Recent studies have shown the reduction in short-term mortality and an increase of hospitalization period in patients who underwent LVP[55], as well as the high probability of their repeated hospitalization within 30 d[56].…”
Section: Treatment Of Ascites In Patients With Cirrhosismentioning
confidence: 99%
“…It is then followed by the administration of diuretic agents and a low sodium diet[54]. Recent studies have shown the reduction in short-term mortality and an increase of hospitalization period in patients who underwent LVP[55], as well as the high probability of their repeated hospitalization within 30 d[56].…”
Section: Treatment Of Ascites In Patients With Cirrhosismentioning
confidence: 99%
“…Only 24.5% of them were from the EP group. Another study conducted by Sobotka et al [ 25 ] found that paracentesis was associated with increased 30-d readmission. Despite this finding, paracentesis is recommended by guidelines and it is a quality indicator in cirrhotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study utilizing the Nationwide Inpatient Sample specifically analyzed readmission rates in patient with decompensated cirrhosis with ascites and determined this specific group of patients had a 30% chance of 30 day readmission. Readmission in these patients was associated with younger age, government funded insurance, multiple comorbidities, nonalcoholic cirrhosis and hepatocellular carcinoma 5 . Another study by Volk et al predict that about 22% of these readmissions could have been prevented by better patient education and intensive outpatient monitoring 8 .…”
mentioning
confidence: 94%
“…One of the most prevalent and early features of decompensation is the development of ascites 4 . The accumulation of ascites with associated discomfort and shortness of breath is one of the top ten reasons for readmission in patients with decompensated cirrhosis 5 . Multiple treatment options exist in the management cirrhosis including fluid and salt restriction, diuretics, large volume paracentesis, transjugular intrahepatic portosystemic shunt (TIPS) and liver transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation